Bi-phase fire-resistant polyethylenimine/graphene oxide/melanin coatings using layer by layer assembly technique: Smoke suppression and thermal stability of flexible polyurethane foams. (29th April 2019) - Shi, Xingxing; Yang, Peng; Peng, Xiangfang; Huang, Chuhao; Qian, Qiangyu; Wang, Bin; He, Jinlin; Liu, Xianhu; Li, Yiwen; Kuang, Tairong
Abstract: In an effort to achieve a high-efficient fire-resistant coating for the flexible polyurethane (PU) foams, a layer-by-layer assembly technique of polyethylenimine (PEI), graphene oxide (GO) and synthetic melanin nanoparticles (SMNPs) was constructed on the surface of PU foams. The preeminent radical scavenging capacity and high-temperature thermal stability of SMNPs enable it to be applied as a flame retardant for the subsequent coating process. Scanning electron microscope (SEM) images indicate that the as-fabricated PEI/GO/SMNPs coatings are uniformly deposited on the PU foam along the cell walls. In contrast with pure and bilayer-coated (BL-coated) PU foams, thermogravimetric analysis (TGA) reveals that the trilayer-coated (TL-coated) foam exhibits a better thermos-oxidative stability and a lower pyrolysis rate with the deposition of PEI/GO/SMNPs nanocoating. In the torch burn test, the flame of PU-1TL foam coated with only one-trilayer PEI/GO/SMNPs is able to self-extinguish and the original shape of the entire foam is intactly preserved. Cone colorimeter tests indicate that the release amount of heat and smoke can be effectively suppressed in the coated foam, and the formation of the highly graphitized char is beneficial to the improvement of the fire-resistant performance. In addition, thermogravimetric analysis/infrared spectrometry (TG-IR) results demonstrate that the volatilization of organic and toxic gases in gas phase are effectively restrained, which can be attributed to the lamellar shield of GO and radical trapping effect of SMNPs. These results illustrate that synthetic melanin material is one of the promising candidates as efficient additive in fire-resistant polymers, and the PEI/GO/SMNPs coatings play a part in gas-solid phase to improve the flame retardancy of PU foams. Graphical abstract: Image 1 Highlights: A surface nanocoating for PU foam is fabricated by layer-by-layer technique. SMNPs exhibit excellent radical scavenging capacity and high-temperature stability. PU-1TL foam achieves self-extinguishing and retains its initial shape under flame. The fire retardancy of foams is remarkably enhanced with the deposited coatings.